Study protocol to develop a core outcome set for thyroid dysfunction to bridge the unmet needs of patient-centred care - Ooi, Cheow Peng; Yusof Khan, Abdul Hanif Khan; Abdul Manaf, Rosliza; Mustafa, Norlaila; Sukor, Norlela; Williamson, Paula R.; Kamaruddin, Nor Azmi (BMJ Group, 2021)
Thyroid dysfunctions (TD) are common medical conditions affecting all global populations. Improved healthcare leading to increasing survival rates and delayed diagnosis rendered significant burden of the disease in the increasing number of patients with TD with comorbid illnesses. Therefore, reducing the burden of TD and improving the quality of care are crucial. Existing poor-quality data that guide evidence-based decisions only provide a fragmented picture of clinical care. The different outcomes across studies assessing the effectiveness of treatments impede our ability to synthesise results for determining the most efficient treatments. This project aims to produce a core outcome set (COS), which embeds the multiple complex dimensions of routine clinical care for the effectiveness studies and clinical care of adult patients with TD. Methods and analysis This mixed-method project has two phases. In phase 1, we will identify a list of patient-reported and clinical outcomes through qualitative research and systematic reviews. In phase 2, we will categorise the identified outcomes using the Core Outcome Measures in Effectiveness Trials taxonomy of core domains and the International Classification of Functioning, Disability and Health. We will develop questionnaires from the list of outcomes identified from each domain for the two-round online Delphi exercise, aiming to reach a consensus on the COS. The Delphi process will include patients, carers, researchers and healthcare participants. We will hold an online consensus meeting involving representatives of all key stakeholders to establish the final COS. Ethics and dissemination The study has been reviewed and approved by the Ethics Committee for Research Involving Human Subjects, Universiti Putra Malaysia and the Research Ethics Committee, National University of Malaysia. This proposed COS in TD will improve the value of data, facilitate high-quality evidence synthesis and evidence-based decision-making. Furthermore, we will present the results to participants, in peer-reviewed academic journals and conferences.